Effectiveness Analysis of Working Capital on MSME Handycraft - Laras Nada Wahyu Atika; Agus Sukoco (Journal of World Conference (JWC), 2019)
This study aims to determine the effectiveness of working capital management in MSME Rozatajaya Souvenir in Sidoarjo through the analysis of liquidity and activity ratios. The research method is using descriptive qualitative. Data obtained from financial transaction records for two semesters of 2018. The results of this study found that the average Liquidity Ratio was very good which included Current Ratio of 3.02, Quick Ratio of 2.93 and Cash Ratio of 2.25. The effectiveness of working capital using the Activity Ratio was considered less effective including the average Working Capital Turnover of 1.23, Receivable Turnover of 4.22 and Turnover Inventory of 14.95 times. The findings of this study, working capital is very necessary for business operations, however, management of working capital is still not effective so it requires a strategy to increase the effectiveness of working capital in business development.